2021
DOI: 10.1177/1321103x211025850
|View full text |Cite
|
Sign up to set email alerts
|

Toward a nuanced understanding of musicians’ professional learning pathways: What does critical reflection contribute?

Abstract: Making sense of musicians’ professional learning pathways is of crucial importance to understanding their career progressions, their routes into creative employment, and the relevance of various policies to their professional lives. However, this is a far cry from understanding how critical reflection catalyzes diverse learning routes, especially when considering evidence originating from postgraduate musicians’ own accounts of their journeys into job creation. In this study, we invited five postgraduate class… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
3

Relationship

4
2

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 47 publications
0
10
0
Order By: Relevance
“…Within social factors, the participants also referred to the strong influence of networks, and how certain attitudes of sociocultural agents surrounding them (e.g., dis-motivated peers) negatively impacted their motivation to be professional musicians. They also highlighted the lack of influence and decision they had on their studying and professional choices, as identified in earlier studies where such decisions and choices are positively/negatively determined by peers, performers, or family members surrounding music students (e.g., López-Íñiguez & Burnard, 2022). have discussed the tension between relying on peers at the same time as competing with them, while acknowledging the value of career preview, mentoring and realistic support and guidance, and access to communities of practice for expanding and developing skills; however, some participants did not see the benefit of seeking advice from other professionals.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Within social factors, the participants also referred to the strong influence of networks, and how certain attitudes of sociocultural agents surrounding them (e.g., dis-motivated peers) negatively impacted their motivation to be professional musicians. They also highlighted the lack of influence and decision they had on their studying and professional choices, as identified in earlier studies where such decisions and choices are positively/negatively determined by peers, performers, or family members surrounding music students (e.g., López-Íñiguez & Burnard, 2022). have discussed the tension between relying on peers at the same time as competing with them, while acknowledging the value of career preview, mentoring and realistic support and guidance, and access to communities of practice for expanding and developing skills; however, some participants did not see the benefit of seeking advice from other professionals.…”
Section: Discussionmentioning
confidence: 90%
“…• Social factors connect musicians’ professional learning pathways with sociocultural influences from peers, performers, family, and other influencers (López-Íñiguez & Burnard, 2022) and to relatedness (i.e., social connectedness) within the self-determination (SDT) framework (Deci & Ryan, 2002), where peer support, interactive motivation, idols in touching distance, or networks are crucial.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…The items included in the final factor for musical calling still reflect the intent of Dobrow and Tosti-Kharas’ (2011) measure that was originally included, insofar as the individual items reflect a passion and commitment to music; differences may relate to our expanded definition of musician as well as the fact that our study represents responses across the lifespan, whereas theirs focused primarily on university students. The inclusion of learning is logical here given the precarity and nonlinearity of music careers and the subsequent need to engage in career-long learning (as evidenced by López-Íñiguez & Bennett, 2020, 2021; López-Íñiguez & Burnard, 2021). The alignment of learning and musical calling points also to the curiosity and creativity that is inherent in creative practice (Taylor & Littleton, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…This might suggest that efficacy beliefs and musical calling are both at the core of musical engagement and intrinsically linked to the motivation to pursue a career in music; it may be, for example, that a strong sense of self-efficacy helps to counteract the potential impact of social comparisons with others (in line with Miksza et al, 2021). We suggest that social aspects might be considered part of an external ecosystem that can support goal achievement—particularly more so when social influencers are a crucial part of the (both negative and positive) learning and career pathways of musicians (López-Íñiguez & Burnard, 2021). This insight also aligns with the research of Spychiger (2017), who found that the social factors in her MUSCI measure were only relevant to the community aspects of musical participation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation